2014
DOI: 10.1371/journal.pone.0086965
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Viral and Host MicroRNAs in the Aujeszky’s Disease Virus during the Infection Process

Abstract: Porcine production is a primary market in the world economy. Controlling swine diseases in the farm is essential in order to achieve the sector necessities. Aujeszky’s disease is a viral condition affecting pigs and is endemic in many countries of the world, causing important economic losses in the swine industry. microRNAs (miRNAs) are non-coding RNAs which modulates gene expression in animals, plants and viruses. With the aim of understanding miRNA roles during the Aujeszky’s disease virus [ADV] (also known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 58 publications
2
32
0
Order By: Relevance
“…However, with few exceptions, all miRNAs were found expressed by both the 5= and 3= arms of their precursor sequences, and as expected, one form was predominant (Table 2). Furthermore, the predominant mature miRNAs encoded by the prv-mir-LLT7 and prv-mir-LLT8 genes were those of the 3= arm, as previously detected (23,48) but not yet annotated in miRBase. To clarify the issue, we revised the nomenclature of all PrV miRNAs by adding the arm of origin information ( Table 2).…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…However, with few exceptions, all miRNAs were found expressed by both the 5= and 3= arms of their precursor sequences, and as expected, one form was predominant (Table 2). Furthermore, the predominant mature miRNAs encoded by the prv-mir-LLT7 and prv-mir-LLT8 genes were those of the 3= arm, as previously detected (23,48) but not yet annotated in miRBase. To clarify the issue, we revised the nomenclature of all PrV miRNAs by adding the arm of origin information ( Table 2).…”
Section: Resultssupporting
confidence: 63%
“…No new PrV miRNAs were identified (Table 2). Furthermore, we did not detect the offset-miRNA (moRNA) encoded by the prv-mir-LLT8 gene previously found in dendritic cells during productive PrV infection, identified as prv-miR-4 (22) or moR-8 (23,48). The PrV miRNAs still are annotated as unique mature sequence in the latest version (v21) of the miRBase database (www .mirbase.org).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Although there are differences in disease outcome and virus shedding between viruses isolated from DS and WS, there was no correlation between the position of the isolates in the phylogenetic tree and virulence even when tests were carried out in vivo [41]. It is possible that aspects of virulence are related to other markers in the genome and other biological characteristics such as viral and host microRNAs [42]. …”
Section: Discussionmentioning
confidence: 99%
“…In the previous two decades, numerous studies have indicated the important role of miRNAs in the regulation of crucial cellular processes, including proliferation, differentiation, migration, apoptosis, metabolism and the stress response (5). miRNAs have been demonstrated to act as key regulators in the pathogenesis of diseases (6)(7)(8)(9)(10)(11), particularly in cancer.…”
Section: Introductionmentioning
confidence: 99%